(3GdCfhGQ GddGeYGJ aj GdcdGe Ydi OdGFd GdNjQGJs - (3CHh RjO YHO GdQMef Hf eMeO GdJGefGQJi GdaGSis; (3YHO Gddg eMeO Hf SdjeGf GdLRhdjs
(3ChdgG (B:s
(3CeG HYO aEfi deG QCjJ cJGH OdGFd GdNjQGJ hThGQb GdCfhGQ GdefShH Edi GdTjN YHO Gddg eMeO Hf SdjeGf GdLRhdi hSejJg HGdCfhGQ GddGeYGJ ai GdcdGe Ydi OdGFd GdNjQGJ s
(3BNQgG (B:s
(3hEfeG GdcdGe Ydi UMI GdEYJbGO hSdGeJg ef GdNdd Ydi cd MGd hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhd eNJdaIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(240) s
Keywords: (3GdeLGejYs